REBRANDING DE LA MARCA CRÉDITOS ECONÓMICOS Y SU IMPACTO EN LA IMAGEN Y POSICIONAMIENTO CORPORATIVO DE LA MARCA CRECOS, EN EL CANTÓN QUEVEDO. - Cervantes Pluas, Valeria Janeth (2024)
The present investigation is entitled Rebranding of the economic credits brand and its impact on the image and corporate positioning of the CRECOS brand, in the Quevedo canton, considering that Rebranding refers to all the strategic and creative changes implemented by a brand to renew its image and attract greater public attention. These changes can be visual, such as the design of a new logo, or conceptual, such as the redefinition of its purpose or values, while the image and corporate positioning, which refers to how the public perceives the brand and what place it occupies in its mind compared to other options in the market. This aspect is crucial since a positive image and clear positioning not only strengthens the loyalty of current customers but also attracts new audiences. The objective of this study was to determine the impact of the rebranding of the economic credits brand on the image and corporate positioning of the CRECOS brand in the Quevedo canton. In order to achieve this, a non-experimental cross-sectional methodological design was used with a descriptive-explanatory scope under a mixed approach with qualitative techniques such as the interview and quantitative techniques such as the survey, whose instruments were two questionnaires, both validated and approved by the tutor teacher, with the results that rebranding implies a modification not only in the visual identity, but also entails a real change within the organization. Likewise, this process consists of transforming the brand image and is a long-term objective, defining it as a change in the identity of a brand and/or an attempt to alter the perception among all the stakeholders of the organization.